Depression in university students: associations with impulse control disorders. (2nd July 2016) - Leppink, Eric W.; Lust, Katherine; Grant, Jon E.
Abstract: Objective: The purpose of this study was to assess the implications of depression in a sample of university students, particularly relating to impulse control disorders. While previous studies have shown high rates of depression among university students, no study to date has assessed whether levels of depression show associations with the incidence of impulse control disorders in this population. Methods: In all, 6000 students participated in the College Student Computer Use Survey. A total of 1717 students completed the scales of interest for this analysis. Participants were assigned to groups based on depression scores: severe ( N = 75), mild/moderate ( N = 647) and none ( N = 995). The three groups were assessed using analysis of variance (ANOVA) or chi-square test. A multinomial logistic regression analysis was used to elucidate associations between depression and impulse control disorder diagnoses. Results: Groups differed across demographic, health and academic variables. The severe depression group reported higher rates of skin-picking disorder, compulsive sexual behaviour and compulsive buying. Conclusion: Results suggest a significant association between depression and impulse control disorders. One possibility is that a facet of impulsivity contributes to both problems, which could be important information for clinicians. Future studies will need to clarify the exact nature of the relationship between depression and impulse control disorders.